The reciprocal relationship between foreign direct investment and Morocco’s foreign trade - GOUMRI Abdelghani; RGUIBI Khalid (International Journal of Scientific Research and Innovative Studies, 2025)
The development of Western and South-East Asian countries has been possible thanks to the massive and diversified FDI received over a very long period, directed towards the innovation and high technology sectors, exporting to foreign markets and thus generating trade surpluses as well as fabulous profits invested locally and elsewhere in search of profitable opportunities. The virtuous circle is then set in motion for the good of the country and its population. Our study focuses on these two variables, FDI and foreign trade, and their reciprocal relationships. The econometric approach used is the cointegration law method and error correction models (ECM). The results obtained highlight the following: - There is no impact of FDI on exports and imports in the short term; - In the long term, there is a real impact between the two variables. Keywords: received FDI – Exports – Imports – High Technology – ARV – ECM – Short term – Long term. Received Date: October 20, 2025 Accepted Date: November 11, 2025 Published Date: December 01, 2025 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/584